Efficacy of lenvatinib in intermediate stage and advanced hepatocellular carcinoma: Results of monotherapy and combination with locoregional treatment. (March 2023) - Giannelli, V.; Chiappino, D.; Villani, R.; Carmenini, E.; D'Ambrosio, C.; Fondacaro, L.; Telesca, C.; Demma, S.; Vano, M.; Sperduti, N.; Recchia, F.; Buffa, V.; et al.
Abstract : Introduction: Lenvatinib is the one of the two mainstay first-line therapy for unresectable Hepatocellular carcinoma (HCC). Combined treatment with locoregional treatment and Lenvatinib has been proposed as an alternative strategy in more advanced disease. Real-world study comparison of efficacy and safety between these two regimens is limited, previous studies suggested a higher response rate from locoregional plus systemic treatment than chemotherapy alone. Aim: In this study, we aimed to evaluate the efficacy of lenvatinib in intermediate and advanced stage HCC. Materials and Methods: 46 patients with Child-Pugh score 5-7 and ECOG PS 0-1 who received Lenvatinib for Intermediate or Advanced stage HCC from April 2020 to October 2022 at our hospital were enrolled. First, landmark analyses were performed to evaluate the association between radiological response and prognosis. Univariate and multivariate analyses were then performed to search for factors contributing to OS and Response Rate. Results: Median age was 72, 5 years, Child-Pugh score was 5 in 35 patients, 6 in 5 patients, 7 in 6 patients. 35 patients were started in the first line Lenvatinib and 11 patients were treated with TACE/TARE during the period of lenvatinib. The median OS in 46 patients were 47 weeks, and the ORR was 62 %, in the best response by mRECIST. In a landmark analysis comparing the responder and non-responder groups, the complete responder group (12%) was treated with combined treatment. Multivariate analysis showed that relative tumor volume, AFP value before induction, first response, and combination of Lenvatinib with locoregional treatment were independent predictors of OS. Conclusion: The efficacy of lenvatinib in the treatment of intermediate/advance stage HCC was favorable. The combination of lenvatinib and locoregional treatment may improve further prognosis, even in those patients who are refractory or unsuitable for TACE.